Evaluation of a Standardized All-Terrain Vehicle Safety Education Intervention for Youth in Rural Central Illinois - Joshua A. Novak; John W. Hafner; Jean C. Aldag; Marjorie A. Getz (SAGE Publishing, 2013)
Background: Although research investigating all-terrain vehicle (ATV) riders and ATV injury patterns has led to support for legislative and educational efforts to decrease injuries in users younger than 16 years, there is little published data regarding the utility of ATV safety education programs. This study investigates the effectiveness of a standardized adolescent ATV safety program in changing the safety knowledge and safe ATV riding practices reported by rural Central Illinois youths. Methods: A convenience sample of 260 rural Central Illinois middle and high school students received an ATV safety presentation with both didactic and interactive features during the 2009-2010 school year. Preintervention and postintervention surveys were distributed and collected by teachers. Survey questions consisted of multiple-choice questions pertaining to demographics, ATV safety knowledge, and ATV riding practices. More than 200 surveys were collected prior to the intervention and 165 surveys were collected 12 to 24 weeks after the intervention. Percentages are reported, with differences in nominal variables tested by χ 2 test and interval variables by t test. Results: Following the intervention, there was a significant increase in the correct response rate for ATV safety knowledge questions (45.2% vs 56.2%, P < .001). For adolescents who reported riding ATVs, both safety gear use (11.8% to 21.2%, P = .05) and helmet use (25.4% to 29.0%, P = .56) increased; changes were not significant. Adolescent ATV riders reporting 2 or more accidents showed a slight nonsignificant decrease (25.2% vs 23.4%, P = .77) between the time of the pretest and posttest. Conclusion: This safety program was effective at increasing ATV safety knowledge but demonstrates limited effect on safe riding practices.